Influences of heat stress on serological response and performance of dairy calves - Larry C. Hollis; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2009)
Objectives of this study were to investigate the possible effects of heat stress on calf growth and the development of active immunity. Eighteen heifer calves born between July 21 and August 24, 2008, were housed in individual hutches, and half of the calves were provided supplemental shade from birth to 8 weeks of age. During this time, milk replacer intake, dry feed intake, and fecal scores were recorded daily. Calf weight and hip and shoulder heights were measured and recorded weekly. The bovine viral diarrhea portion of the vaccine given at 5 weeks of age was used as an indicator to track the development of humoral immunity. Intake, growth, temperature response after vaccination, and serum titers did not differ significantly between treatments. In contrast, differences in hutch temperature, relative humidity, and temperaturehumidity index were observed between treatments. Results indicated that supplemental shade provided to calves housed in hutches does not affect their performance or ability to develop active immunity.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Growth; Heat stress; Health; Shade